Nutritional status of animals in peri-urban dairy complexes in Punjab, India - BAKSHI, M P S; WADHWA, M; HUNDAL, J S (The Indian Journal of Animal Sciences, 2010)
The study was taken up to assess the nutritional status of dairy animals in peri-urban dairy complexes in Punjab, India. About 24 to 29 dairy houses were selected randomly from each of Ludhiana (LDC), Amritsar (ADC), Jalandhar (JDC), Ferozepur (FDC) and Hoshiarpur (HDC) peri-urban dairy complexes. Buffaloes predominated in almost all peri-urban dairies, except in FDC. The animals of FDC had the lowest (P